Addressing low core competency of sales admin department: An action research on building enabling work process through initiating and implementing personal action learning - Reyes, Abel Catapang (Animo Repository, 2018)
This Integrated Action Research addressed the issue of low core competency of the team members of Sales Administration Department of ABC Financial Services Philippines Corp. with the ultimate goal of developing a culture of continuous improvement or what is commonly known as Kaizen. The objectives of this paper include changing the perspective of the team members to Kaizen through personal action learning and reflection and for them to initiate change out of their own volition. This paper also wants to improve the problem-solving skills of the team members through the development of Idea Generation System or Soi Kufu. This will enable the organization to improve its processes. Issue was identified through one-on-one interviews, formal and informal meetings, and action research tools such as ORJI, ladder of inference, levels of inquiry, hypothesis thesis, four parts of speech, and force field analysis. Guided by Personal Action Learning Model, and GROW Model, we determined that the interventions were deemed appropriate to address the issue through Lunch and Learn sessions in the first cycle to change the perception of the team members to Kaizen and creation of Idea Generation System or Soi Kufu to guide the team members in their efforts to change. In addition, Lewins Unfreeze-Change-Refreeze model was used to guide the changes done by the team throughout this action research. Through constant collaboration, the team and I were able to increase engagements of the team to Kaizen thereby addresses the low core competency.